Development of a quality of life instrument to evaluate oral mucositis in cancer patients (Research, Society and Development, 2023)
Oral mucositis is a side effect of cancer treatments, a limiting condition and of great impact on quality of life (QOL). The objective was to develop an instrument to evaluate QoL related to oral mucositis. Research through mixed methods, starting with qualitative interviews analyzed by the Bardin method and Reinert method, with the IRaMuTeQ software, followed by the Delphi method in four rounds of interviews and discussions with experts. The first version of the instrument underwent a pre-test with 10 patients, with quantitative and qualitative analysis, followed by another round of experts. The material of the qualitative interviews pointed out the terms pain and feeding as central in the experience of oral mucositis, besides providing several keywords for definition of constructs. Then 4 experts formulated 34 questions sent to 10 other experts from different regions and Brazilian institutions who analyzed the clarity, spelling and need of each question for the questionnaire. The relevant changes were made, reviewed and discussed again. The first version of the Oral Mucositis Impact Scale in Cancer Patients (EIMOPO) was presented to 10 patients who did not participate in the qualitative interviews and answered the degree of understanding and need of each question. The final analysis of the pre-test reformulated some tenses and words difficult to understand, forming the final version of the instrument. Although there are good instruments to measure QoL and oral mucositis, we present new questions about financial impacts, treatment interruption, saliva alteration, weight loss directly related to oral mucositis and psychosocial aspects.